2019
DOI: 10.1136/jnnp-2018-318996
|View full text |Cite
|
Sign up to set email alerts
|

Open-label trial of anterior limb of internal capsule–nucleus accumbens deep brain stimulation for obsessive-compulsive disorder: insights gained

Abstract: BackgroundFor more than 15 years, deep brain stimulation (DBS) has served as a last-resort treatment for severe treatment-resistant obsessive-compulsive disorder (OCD).MethodsFrom 2010 to 2016, 20 patients with OCD (10 men/10 women) were included in a single-centre trial with a naturalistic open-label design over 1 year to evaluate the effects of DBS in the anterior limb of the internal capsule and nucleus accumbens region (ALIC-NAcc) on OCD symptoms, executive functions, and personality traits.ResultsALIC-NAc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 27 publications
0
62
0
Order By: Relevance
“…Examples that utilized group statistics span across different diseases like PD (Bouthour et al, 2019;Horn et al, 2019c), essential tremor (Al-Fatly et al, 2019;Kroneberg et al, 2019), Dystonia (Neumann et al, 2017), Meige syndrome (Yao et al, 2019), OCD Huys et al, 2019), epilepsy (Middlebrooks et al, 2018;Wang et al, 2019), Tourette's Syndrome (W. J. or refractory thalamic pain syndrome (Levi et al, 2019). Using Lead-DBS, a sweet spot for STN-DBS in PD was defined and used to predict improvement of motor symptoms in out-of-sample data (Dembek et al, 2019a).…”
Section: A Tool To Shift Dbs Imaging Research To a Group Levelmentioning
confidence: 99%
“…Examples that utilized group statistics span across different diseases like PD (Bouthour et al, 2019;Horn et al, 2019c), essential tremor (Al-Fatly et al, 2019;Kroneberg et al, 2019), Dystonia (Neumann et al, 2017), Meige syndrome (Yao et al, 2019), OCD Huys et al, 2019), epilepsy (Middlebrooks et al, 2018;Wang et al, 2019), Tourette's Syndrome (W. J. or refractory thalamic pain syndrome (Levi et al, 2019). Using Lead-DBS, a sweet spot for STN-DBS in PD was defined and used to predict improvement of motor symptoms in out-of-sample data (Dembek et al, 2019a).…”
Section: A Tool To Shift Dbs Imaging Research To a Group Levelmentioning
confidence: 99%
“…Case reports and open studies have reported that about 50% of OCD patients respond favorably to ALIC-DBS (64 -68). A recent open-label study, including the largest cohort of 20 refractory OCD patients stimulated in the ALIC, reported 40% of responders 1 year after surgery (68). Adverse events were limited to one case due to hardware infection, and transient effects due to DBS settings, such as hypomania, disinhibition, lack of concentration, transient loss of energy, sleep disturbances, and >20% weight gain (68).…”
Section: Striatal Region Anterior Limb Of the Internal Capsulementioning
confidence: 99%
“…A recent open-label study, including the largest cohort of 20 refractory OCD patients stimulated in the ALIC, reported 40% of responders 1 year after surgery (68). Adverse events were limited to one case due to hardware infection, and transient effects due to DBS settings, such as hypomania, disinhibition, lack of concentration, transient loss of energy, sleep disturbances, and >20% weight gain (68). If the clinical effects of ALIC-DBS on refractory OCD were encouraging, a confirmation level I study is still needed (69).…”
Section: Striatal Region Anterior Limb Of the Internal Capsulementioning
confidence: 99%
See 1 more Smart Citation
“…This study included data from ten patients (5 females) with refractory and severe (Yale-Brown Obsessive Compulsive Scale [YBOCS] 25) OCD that were being treated with DBS implants in the VC/VS (for details on study design and recruitment see Ref. [7]). Patients underwent bilateral stereotactic implantation of quadripolar leads (Model 3387 or 3389 DBS Lead; Medtronic; Minneapolis, MN, USA) with the two most ventral/distal contacts targeting the VS and two most dorsal/proximal contacts located in the VC (Fig.…”
mentioning
confidence: 99%